Men's perception of information and descriptions of emotional strain in the diagnostic phase of prostate cancer-a qualitative individual interview study - Maja Elisabeth Juul Søndergaard; Kirsten Lode; Svein Reidar Kjosavik; Sissel Eikeland Husebø (Taylor & Francis Group, 2021)
Objective To explore men`s perception of information and their possible emotional strain in the diagnostic phase of prostate cancer. Design, setting, patients A qualitative explorative research design was employed. Data were collected from June to November 2017. The study was set at a urological outpatient clinic at a university hospital in Norway. Semi-structured interviews were conducted with ten men who had been examined for prostate cancer. Interviews were analyzed using Systematic Text Condensation (STC). Results The analysis revealed three themes. The theme 'Different needs and perceptions of information' illustrated that information should be personalized. Despite different information needs, insufficient information about prostate cancer may prevent some men from being involved in decisions. The theme, 'A discovery of not being alone', indicated that a sense of affinity occurs when men realize the commonality of prostate cancer. Some men benefited from other men's experiences and knowledge about prostate cancer. The last theme 'Worries about cancer and mortality' showed that the emotional strain was affected by men's knowledge of cancer and the received information. Men expressed conflicting feelings toward prostate cancer that could be difficult to express. Conclusions The findings indicate that men in the diagnostic phase of prostate cancer are not a homogeneous group, but need personalized information. Some men may benefit from other men's experiences and support. Men's emotional strain can affect their communication about prostate cancer, which should be acknowledged. Procedures that identify patients' information needs early on should be an integrated part of the diagnostic phase of prostate cancer.KEY POINTS Knowledge about men's information needs and possible emotional strain in the diagnostic phase of prostate cancer are limited. Men with suspected prostate cancer have different preferences and information needs; however, insufficient information prevents men from participating in decisions. Men experience a sense of affinity with other men affected by prostate cancer, and some men benefit from exchanging experiences. Men consider prostate cancer as a less aggressive type of cancer but may experience emotional strain.